Особливості регіонального менталітету в контексті становлення української політичної нації (на прикладі Мелітополя) - Букрєєва, Ірина Вікторівна; Букреева, Ирина Викторовна; Bukrieieva, Iryna V. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано регіональні особливості менталітету мешканців Мелітополя як типового міста Південного Сходу України крізь призму таких атрибутивних елементів, як ідентичність, цінності, почуття, соціальні-політичні орієнтації. Відмінними рисами менталітету мешканців міста є законослухняність і низька громадянська активність, пріоритет колективної думки над індивідуальною, цінності групової належності. Водночас під впливом зовнішніх суспільно-політичних факторів відбуваються процеси трансформації свідомості місцевої громади, що проявляється в усвідомленні своєї загальнонаціональної приналежності, баченні спільного майбутнього на основі реформування економічного життя та громадянських цінностей. The features of the regional manifestations of mentality of the typical of the town South- East of Ukraine Melitopol are represented on the basis of empirical data. The aim of the study is to identify regional differences in some features of the mentality of the inhabitants of the city of Melitopol, objectively impede systemic transformation in the present stage of development of society. The results of the survey revealed that a significant portion of residents have low social activity, focus on collectivism and industrial values of the Soviet era, at the same time quick speed is a perceived need in the consolidation of society, common economic interests, national identity. Along with universal values of the respondents noted this trait mentality as tolerance, indicating that the production community, special socio-cultural practices of intercultural cities, which are realized by the residents and have significant potential for development. The results of the study can be taken into account when analyzing a single objective determinant of the formation of alland specifically-regional mental specifics and to contribute to more sophisticated political and practical measures to ensure national unity.
Features of the Regional Mentality in the Context of the Formation of the Ukrainian Political Nation (the example of Melitopol)
Keywords: менталітет; ідентичність; цінності; консолідація; громадянська культура; mentality; identity; values; consolidation; civil culture